BASIC annual review and planning meeting - Interview with Lawrence Kent - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
BASIC annual review and planning meeting 2019 Held at IITA Ibadan, 11th - 13th March, 2019.